RELEVANSI NILAI-NILAI PENDIDIKAN KARAKTER DALAM SURAH ALI-IMRAN 159-160 - Awaliah, Fuji; Al Khadziq, Muhammad Fuadzy; Lessy, Zulkipli (TAZKIRAH, 2025)
Relatively Islamic character education is similar to moral education (akhlaq), in which purifying the soul is maintained because the main purpose man character’s creation is a submission to Allah. The objective of the research to explore the character education improvement and its implementation. In Islam, such an education is an effort to form good character as stated in Surah Ali-Imran verses 159-160. This study uses a qualitative method in that it is attempts to understand phenomena in the surrounding environment and to explore books, journal articles, and reviews of previously published research. The result of this research is that character education is to intentionally cultivate virtues in people like the Prophet Muhammad has who is a role model for humans. While the values of character education in Islam are taqwa (fear of God), tawakkal (trusting in God’s plan), responsible, tolerance, honest, discipline, hard work, curiosity, peace-loving, gentle, forgiving each other, deliberation (musyawarah), and helping each other. In short, according to Al-Misbah exegesis, the values of character education illustrated in the Surah Ali-Imran verses 159-160 include: gentleness, mutual forgiveness, deliberation, tawakkal to Allah, and helping each other. Secara relatif, pendidikan karakter dalam Islam sama dengan pendidikan akhlak, dimana penyucian jiwa diutamakan karena tujuan penciptaan karakter manusia adalah untuk berbakti kepada Tuhan. Artikel ini bertujuan untuk mengeksplor peningkatan pendidikan karakter dan pelaksanaannya. Pendidikan karakter dalam Islam mengarahkan pencapaian seseorang pada karakter yang baik sebagaimana terdapat dalam surat Ali-Imran ayat 159-160. Penulisan artikel ini menggunakan metode penelitian kualitatif dengan upaya memahami fenomena dalam lingkungan sekitar, buku, artikel jurnal, maupun laporan hasil penelitian terdahulu. Hasil dari penelitian ini adalah pendidikan karakter menuntut manusia untuk berbudi luhur seperti Nabi Muhammad yang merupakan suri teladan bagi manusia. Sedangkan nilai-nilai pendidikan karakter dalam Islam yaitu taqwa, tawakkal, bertanggung jawab, toleransi, jujur, disiplin, kerja keras, rasa ingin tahu, cinta damai, lemah lembut, saling memaafkan, musyawarah, dan tolong-menolong. Ringkasnya, nilai pendidikan karakter yang dijelaskan dalam surat Ali-Imran ayat 159-160 perspektif tafsir Al-Misbah adalah lemah lembut, saling memaafkan, bermusyawarah, tawakkal kepada Allah, dan tolong-menolong